(untitled) (Medicine Today, 2017)
COPD is one of the major cause of chronic morbidity and mortality throughout the world. Among the extra pulmonary effects of COPD cardiovascular disorders are significant. Although its silent involvement is known, but little attention paid to this major comorbidity while treating these group of patients. To assess the cardiovascular risk even in stable COPD patients their systolic blood pressure (SBP), diastolic blood pressure (DBP), pulse pressure (PP), mean arterial pressure (MAP) were observed and correlated these with the severity of airflow limitation (FEV1). This crosssectional study was carried out in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from January to December, 2010. For this purpose 60 (sixty) male, smoker (5-10 pack year) patients of stable COPD (FEV1/FVC% <0.70; FEV1?80%; without any exacerbation for last 4 weeks) were randomly selected from the Out Patient Department (OPD) of the Cardiovascular unit of the Department of Cardiology, BSMMU and also from a private clinic in Dhaka. On the basis of spirometric (group B2) of COPD patients with age 35-45 years were included in this study. In addition, 30 age, BMI, serum lipid profile and smoking status matched apparently healthy male persons were studied as control (group A). SBP, DBP, PP and MAP (by sphygmomanometer and stethoscope) were measured and calculated. Data were expressed as mean±SD. For statistical analysis Independent sample t-test and Pearson’s Correlation Coefficient test were performed, as applicable and p<0.05 was accepted as significant. Significantly (p<0.001) higher SBP, DBP, PP and MAP were found in moderate stage (group B2) than those of control and mild stage (group B1) of COPD patients. In addition, 4 types of BP were negatively correlated with FEV1 in moderate stage and were statistically significant for SBP (p<0.01), PP and MAP (p<0.05). This study reveals that, cardiovascular function status may be altered even in stable COPD and this alteration is inversely related to the severity of the disease. Medicine Today 2016 Vol.28(1): 17-21